Trends in Use of Acupuncture During Pregnancy for the Military Health System, 2006–2016 - Madsen, Cathaleen (Med Acupunct, 2019)
Objective: Acupuncture is recognized as safe for use in pregnancy when correctly performed and has been provided at military healthcare facilities since 2005. Previous research identified a number of pregnant patients receiving acupuncture within the Military Health System (MHS). This study was conducted to describe trends in usage from 2006 to 2016 including patient and provider characteristics. Materials and Methods: This study utilized TRICARE claims from the MHS Data Repository (MDR). Analysis was performed through the MDR for women ages 18 years and older, who had acupuncture treatments at military treatment facilities related to pregnancy, from 2006 to 2016. Descriptive statistics were collected on patient demographics, clinic types and provider specialties, major diagnostic categories associated with acupuncture, number of visits per patient, and utilization over time. Results: Less than 0.3% of pregnant women in the MHS received acupuncture. The greatest usage was among patients who were white, ages 25–34, dependents of active duty personnel, and in the Army service. The most common diagnoses were for musculoskeletal system and connective tissue disorders (41.9%). Approximately 79% of care was delivered by physicians. The trend over time rose from 11 visits in 2006 to 130 visits in 2016. Conclusions: Provision of acupuncture in pregnancy grew ∼12-fold between 2006 and 2016, although usage remains low overall. This greater proportion of physician-provided care in pregnant women versus the general patient population may reflect a cautionary attitude toward use in pregnancy. This research is expected to inform discussions for people seeking to increase access to acupuncture during pregnancy.